Analysis of vibrator for sompoton using cantilever beam model - Wong, Tee Hou; Ngu, M.C.D; Chang, Jackson Hian Wui; Jedol Dayou; Liew, Willey Yun Hsien (Universiti Malaysia Sabah, 2013)
One of the famous heritages in Sabah is the traditional musical instrument called sompoton. This instrument has several parts with the vibrator being the most important of all. In this paper, the vibrator is modeled as a cantilever beam with uniformly distributed mass. Using this model, the fundamental frequency is analyzed using Rayleigh’s energy theory. The vibrator made from aluminum is fabricated at different dimensions and is excited using constant air jet to obtain its fundamental resonance frequency. The measured fundamental frequency is then compared with the theoretical values calculated based on cantilever beam model and Rayleigh’s energy theories. It was found that the experimental and theoretical results exhibit the same trend but differ in magnitude. To overcome this, a correction factor is added to the theoretical formulation to account for fabrication error.